Caged-Ball Mitral Prosthesis Explanted After 50 Years - Masiello, Paolo (JACC Case Rep, 2021)
We report a unique case of a Starr-Edwards prosthesis (model 6310, cloth covered) implanted in the mitral position by Christian Barnard that was successfully explanted and replaced after 50 years, the longest period free from valve dysfunction ever reported. Reoperation also included replacement of the native aortic valve combined with tricuspid valve annuloplasty. (Level of Difficulty: Beginner.)